Analisis Yuridis Terhadap Pendaftaran Peralihan Hak Atas Tanah dalam Mewujudkan Kepastian Hukum (Studi Penelitian di Kantor Badan Pertanahan Nasional Kota Batam) - Anida, Anida; Erniyanti, Erniyanti; Nofrial, Ramon; Respationo, Soerya (UNES Law Review, 2023)
This research entitled "Juridical Analysis of Land Rights Transfer Registration in Realizing Legal Certainty (Research Study at the Office of the National Land Agency Batam City)" was conducted because there is a discrepancy between what has been regulated in the applicable laws and what occurs in the field. In practice, the Land Deed Official cannot fulfill the registration period for the deed of transfer of land rights as stipulated in Article 40 paragraph (1) of Government Regulation Number 24 of 1997 concerning Land Registration. This research aims to determine the legal regulations for land rights transfer registration, implementation related to land rights transfer registration, and factors that become obstacles and solutions related to land rights transfer registration. This research was conducted using juridical and empirical legal research. Based on the results of interviews and research, there are factors that hinder Land Deed Official from fulfilling the provisions of applicable laws and regulations, including regarding procedures for buying and selling land and buildings that occur in the field and regarding provisions determined by local government agencies. For this reason, it is hoped that the government can adapt the regulations made to existing regulations and adapt them to conditions occurring in the field.